Changes in the societal burden caused by sleep apnoea in Finland from 1996 to 2018: A national registry study - Mattila Tiina; Hasala Hannele; Kreivi Hanna-Riikka; Avellan-Hietanen Heidi; Bachour Adel; Herse Fredrik; Leskelä Riikka-Leena; Toppila-Salmi Sanna; Erhola Marina; Haahtela Tari; Vasankari Tuula (Elsevier Ltd, 2022)
Background
In the current century, sleep apnoea has become a significant public health problem due to the obesity epidemic. To increase awareness, improve diagnostics, and improve treatment, Finland implemented a national sleep apnoea programme from 2002 to 2010. Here, we present changes in the societal burden caused by sleep apnoea from 1996 to 2018.
Methods
National register data were collected from the Care Register for Health Care, Statistics Finland, the Social Insurance Institution of Finland, and the Finnish Centre for Pensions. Disease prevalence, use of healthcare and social services, and societal costs were estimated.
Findings
The number of sleep apnoea patients increased in secondary care from 8 600 in 1996 to 61 000 in 2018. There was a continuous increase in outpatient visits in secondary care from 9 700 in 1996 to 122 000 in 2018 (1 160%) and in primary care from 10 000 in 2015 to 29 000 in 2018 (190%). Accordingly, the cumulative annual number of days off work for sleep apnoea increased from 1 100 to 46 000. However, disability pensions for sleep apnoea decreased from 820 to 550 (33%) during the observation period. Societal costs per patient decreased over 50% during the observation period (€2 800 to €1 200).
Interpretation
The number of sleep apnoea patients in Finland increased remarkably during the observation period. To control this burden, diagnostic methods and treatment were revised and follow up was reorganised. Consequently, there was a significant decrease in societal costs per patient. The decrease in disability pensions suggests earlier diagnosis and improved treatment. The national sleep apnoea programme was one of the initiators for these improved outcomes.
Funding
The Finnish Institute for Health and Welfare and the Hospital District of Helsinki and Uusimaa (HUH), Helsinki, Finland.